Methylation of suppressor of cytokine signalling 1 gene promoter is associated with acute‐on‐chronic hepatitis B liver failure. Issue 3 (21st July 2014) - Zhang, J.‐J.; Fan, Y.‐C.; Zhang, Z.‐H.; Han, J.; Wang, L.‐Y.; Li, T.; Zhang, F.; Yin, Y.‐P.; Hu, L.‐H.; Yang, Y.; Sun, F.‐K.; Wang, K.
Summary Suppressor of cytokine signalling 1 (SOCS1) was demonstrated to play an important negative role in fulminant hepatitis and might be involved in acute‐on‐chronic hepatitis B liver failure (ACHBLF). This study was therefore to identify the potential role of SOCS1 and its promoter methylation pattern in ACHBLF patients. Sixty ACHBLF patients, 60 chronic hepatitis B (CHB) patients and 30 healthy controls were investigated in this study. We found that expression of SOCS1 mRNA in CHB and ACHBLF patients was significantly higher than that in healthy controls. The serum level of IL‐6, IFN‐γ and TNF‐α was significantly higher in ACHBLF than CHB. Increased serum level of IL‐6, IFN‐γ and TNF‐α was correlated with total bilirubin, ALT, PTA and MELD scores in ACHBLF. The degree of methylation of the SOCS1 in ACHBLF patients (35.0%, 21/60) was significantly higher than that in CHB patients (16.7%, 10/60). Furthermore, methylated group showed lower level of SOCS1, and higher MELD scores and mortality rate when compared with unmethylated group of ACHBLF. These results suggested that SOCS1 might contribute to immune‐related liver damage in ACHBLF, and its aberrant methylation may be a key event for the prognosis of ACHBLF.